Coronavirus disease 2019 vaccine effectiveness among a population-based cohort of people living with HIV. (1st December 2022) - Chambers, Catharine; Samji, Hasina; Cooper, Curtis L.; Costiniuk, Cecilia T.; Janjua, Naveed Z.; Kroch, Abigail E.; Arbess, Gordon; Benoit, Anita C.; Buchan, Sarah A.; Chung, Hannah; Kendall, Claire E.; Kwong, Jeffrey C.; et al.
Abstract : Objective: People with HIV were underrepresented in coronavirus disease 2019 (COVID-19) vaccine clinical trials. We estimated vaccine effectiveness (VE) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection for the BNT162b2, mRNA-1273, and ChAdOx1 vaccines among a population-based cohort of people with HIV in Ontario, Canada. Design: Test-negative design Methods: We identified people with HIV aged ≥19 years who were tested for SARS-CoV-2 by RT-PCR between December 14, 2020 (first availability of COVID-19 vaccines) and November 21, 2021 (pre-Omicron circulation). Outcomes included any infection, symptomatic infection, and COVID-19-related hospitalization/death. We compared the odds of vaccination between test-positive cases and test-negative controls using multivariable logistic regression with adjustment for age, sex, region, calendar time, SARS-CoV-2 test histories, influenza vaccination, comorbidities, and neighborhood-level socio-economic status. VE was derived as (1 – adjusted odds ratio) × 100%. Results: Among 21 023 adults living with HIV, there were 801 (8.3%) test-positive cases and 8, 879 (91.7%) test-negative controls. 20.1% cases and 47.8% of controls received ≥1 COVID-19 vaccine dose; among two-dose recipients, 93.4% received ≥1 mRNA dose. Two-dose VE ≥7 days before specimen collection was 82% (95% confidence interval [CI] = 74–87%) against any infection, 94% (95% CI = 82–98%) against symptomatic infection, and 97% (95% CI = 85–100%) against hospitalization/death. Against any infection, VE declined from 86% (95% CI = 77–92%) within 7–59 days after the second dose to 66% (95% CI = −15–90%) after ≥180 days; we did not observe evidence of waning protection for other outcomes. Conclusion: Two doses of COVID-19 vaccine offered substantial protection against symptomatic illness and hospitalization/death in people with HIV prior to the emergence of the Omicron variant. Our findings do not support a broad conclusion that COVID-19 VE is lower among people with HIV in populations that, for the most part, are attending HIV care, taking antiretroviral medication, and are virally suppressed.